Constitutional Recognition of Adat Law Communities to Create Legal Certainty - Nurus Zaman; Nia Kurniati; Raphael D. Jackson- Ortiz (Journal of Indonesian Constitutional Law, 2026)
This study aims to determine the state's legal politics on the conditional recognition of Adat Law Communities (ALCs) under the 1945 Constitution, which remains uncertain, leading to acts of violence and discrimination. This study contributes to providing stakeholders with an understanding that every state's legal politics must be based on the principle of a unitary state as stipulated in the 1945 Constitution, with implications for the recognition of ALCs. This study uses a doctrinal legal method with a statute and conceptual approach. The findings of this study are that, so far, the government considers conditional legal politics regarding state recognition of ALCs to be the right choice in a unitary state, namely, one without independent collective power. Furthermore, violations of the ALCs under Article 18B paragraph (2) of the 1945 Constitution, particularly those related to the principle of a unitary state, are unclear because the scope of a unitary state is not constitutionally regulated. However, if such violations are deemed breaches, the state has the authority to revoke the existence of these ALCs. The conclusion of this study is that the state's political law choices, as reflected in constitutional regulations, must be clearly defined to uphold the value of legal certainty. The formulation of legal norms in Article 18B paragraph (2) of the 1945 Constitution should not require the existence of ALCs, as the parameters of the unitary state are clearly regulated in the constitution.